Observational study of maternal anthropometry and fetal insulin. Issue 2 (1st September 1999) - Soltani-K, H; Bruce, C; Fraser, R B
Abstract : AIMS: To examine the relation between maternal body fat and fetal metabolism. METHODS: In this observational study, cord blood samples were collected from 60 infants of healthy women for the measurement of insulin and C peptide concentrations. Maternal weight, height, body mass index (BMI) and body composition (skinfold thickness measurements and bioelectrical impedance) were assessed at 13–15 weeks of gestation. Twenty five of the volunteers agreed to have a 75 g oral glucose tolerance test at 28–31 weeks of gestation. RESULTS: Positive correlations were observed with both cord insulin or C peptide concentrations and maternal early pregnancy BMI (r=0.44, p=0.002 and r=0.33, p=0.008, respectively). There was no significant correlation between cord insulin or C peptide concentrations and birthweight or birth weight centiles. CONCLUSION: Maternal BMI could be a predictor of fetal cord insulin concentration.